The Salep Tarjhe Tradition in Madurese Customary Marriage Prohibitions: A Perspective Based on Al-Ghazali’s Concept of Maslahah Mursalah - Raja Faisal; Nasrulloh Nasrulloh; Nur Mahmudah; Jimmy Malintang; Khoirul Hidayah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
The tradition of salep tarjhe is one of the marriage prohibitions of the Madurese community in Puguk Village that continues to be preserved as a customary rule because it is believed to cause various adverse effects on married couples who violate it. However, in Islamic law, there is no explicit textual evidence prohibiting this practice. This study aims to examine the prohibition of the salep tarjhe tradition in Madurese customary marriages in Puguk Village, as well as to analyze it using the theory of maslahah mursalah from Al-Ghazali’s perspective. This is a field study (field research) employing a qualitative approach conducted in Puguk Village, Sungai Ambawang Subdistrict, Kubu Raya Regency, West Kalimantan. Data sources consist of primary and secondary data. Data collection was conducted through interviews and documentation, then analyzed using the Miles and Hubberman model, which includes the stages of data reduction, data presentation, and drawing conclusions and verification. Research informants included community leaders, religious leaders, and traditional practitioners. The results of the study indicate that the salep tarjhe tradition is a practice prohibiting marriage between male relatives on the wife’s side and female relatives on the husband’s side, which is believed to cause negative consequences for couples who violate it, such as financial hardship, domestic conflict, and even premature death. From the perspective of Al-Ghazali’s maslahah mursalah, salep tarjhe does not yet meet the requirements set forth by Al-Ghazali, namely that it must be in harmony with the maqasid al-shari’ah, be dharuriyyah, qath’iyyah, and kulliyah, and not contradict textual evidence. The public interest inherent in the tradition of salep tarjhe is only at the level of tahsiniyyat, and thus cannot yet be categorized as Al-Ghazali’s maslahah mursalah.